Face-Inversion Effect on Disgust Evoked by a Cluster of Dots. (June 2018) - Furuno, Manami; Sakurai, Yuri; Imaizumi, Shu; Koyama, Shinichi
A cluster of dots such as lotus seed pods evokes extremely strong disgust when it is placed on human and animal skins. However, few empirical studies have examined the role of the background image, such as skin, in the generation of disgust. In this study, we investigated whether the orientation of background faces influences the disgust evoked by the dot pattern. The participants were asked to evaluate disgust to an upright, inverted, or phase-scrambled face image with or without a cluster of dots on it and then complete a questionnaire measuring trypophobia proneness (Trypophobia Questionnaire). The results suggested that disgust was intensified by the background faces, especially by the upright faces. The intensification of disgust in the upright face was correlated positively with the Trypophobia Questionnaire scores. The results indicated a face-inversion effect on the disgust to the dot pattern, suggesting a significant role of the background image.